Aspectos tributários da implementação das Normas Internacionais de Contabilidade (IFRS) no Brasil: uma nova abordagem a partir da perspectiva do direito e desenvolvimento - Campedelli, Laura Romano (2016)
This paper aims to propose a new approach to the tax aspects involved in the implementation of international accounting standards (IFRS) in Brazil, based on the theoretical framework of law and development. After presenting the international accounting harmonization movement and the contextualization of the historical and legislative evolution in the implementation of IFRS in Brazil, is held a literature review from the national legal and tax doctrine, about the impacts that arise from the use of new accounting standards for tax matters, identifying four kinds of problems: (i) qualification problems, related to the use of the "substance over form" principle; (ii) problems related to temporal conflicts at the recognition moment of accounting and tax results; (iii) problems related to the emergence of legal gaps and; (iv) problems related to the subjectivism of the new accounting standards. Following is argued that this strictly 'legal and tax' approach on the subject, named in this paper as a "legal and tax perspective', has led to the idea that the IFRS would be the bearers of complexities and insecurities that permeates the brazilian taxation, which may represent a narrow analysis paradigm for the issue. From the legal and institutional perspective, typical of the law and development approach, the paper presents a new analysis paradigm for the theme, classifying the IFRS implementation movement in Brazil as a process of institutional reform and developing the hypothesis that the problems presented by the legal and tax doctrine are only symptoms of the existence of a path dependence in tax matters in Brazil, concept of law and development literature which means "dependency of the previous institutional trajectory'. The adoption of this distinct analysis referential has the scope to increase the debate, making room to reframe the problems presented by tax doctrine and consider the legal and institutional re-accommodations that may be necessary in the national tax system in favor of a greater demand for development: align brazilian accounting practices to international practices, using the tax system as an element that enables this change, not as a barrier designed to prevent it.